2005
DOI: 10.1103/physrevlett.94.026803
|View full text |Cite
|
Sign up to set email alerts
|

Molecules on Insulating Films: Scanning-Tunneling Microscopy Imaging of Individual Molecular Orbitals

Abstract: Ultrathin insulating NaCl films have been employed to decouple individual pentacene molecules electronically from the metallic substrate. This allows the inherent electronic structure of the free molecule to be preserved and studied by means of low-temperature scanning-tunneling microscopy. Thereby direct images of the unperturbed molecular orbitals of the individual pentacene molecules are obtained. Elastic scattering quantum chemistry calculations substantiate the experimental findings.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
869
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 812 publications
(906 citation statements)
references
References 25 publications
33
869
0
4
Order By: Relevance
“…2e,f). These features show a molecular orbital-like electronic density and a periodicity of about 2.4 Å between bright lobes 28 . This distance corresponds to the lattice constant of graphene, indicating that these structures consist of a concatenation of benzene rings (see Supplementary Note 2 and Supplementary Figs 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…2e,f). These features show a molecular orbital-like electronic density and a periodicity of about 2.4 Å between bright lobes 28 . This distance corresponds to the lattice constant of graphene, indicating that these structures consist of a concatenation of benzene rings (see Supplementary Note 2 and Supplementary Figs 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…Franke et al have recently reduced the electronic coupling of C 60 with a metal surface by locking and lifting each fullerene with a second molecular species [7]. Furthermore, it has been shown that, upon adsorption of molecules on ultrathin NaCl films on metal surfaces, inherent electronic and optical properties of individual molecules can be studied [8][9][10]. However, to our knowledge, there are only three published STM studies on the growth of two-dimensional molecular islands on insulating NaCl layers, two of them on metal-containing porphyrine molecules [11,12], and the third one on C 60 molecules [13].…”
Section: Introductionmentioning
confidence: 99%
“…[19,34,38] The large lateral separation of the highly reactive Si "up" atoms on the silicene surface may be key to minimizing the hybridization between the Pc ligands and the silicene surface, in contrast to the case of other π-conjugated organic molecules on conventional Si surfaces. [16,18] Therefore, despite the small variation in binding configuration, which suggests the molecule is strongly pinned, the molecule retains localized states that resemble the states of the isolated molecule.…”
mentioning
confidence: 99%